Perceptions Of College Students’ Academic Motivation And Higher Order Thinking Skills In The Context Of Outcome-based Education Within Hybrid Learning In China - Zheng, Zheng (2024)
Academic motivation and higher order thinking skills are the dual engines driving the learning process of college students in China which is undergoing a period of hybrid teaching environment. Yet, it lacks a reliable approach to apply instructional strategies to determine the perception and relationship of academic motivation and higher order thinking skills. In addition, outcome based education (OBE) provides a strong theoretical foundation for this study. This study intends to examine students' perceptions of a hybrid learning curriculum, academic motivation, and higher order thinking skills following an OBE-based hybrid learning model. This study also investigates the relationship of students' academic motivation (intrinsic motivation, external motivation and amotivation) and higher order thinking skills (analyzing, evaluating, creating, problem solving and critical thinking) within the teaching intervention. This study analyzed the adoption of an explanatory sequential mixed approach using three surveys and focus group interviews. The research selected 150 undergraduate students from eight different majors at a selected University by using stratified sampling. Subsequently, follow-up interviews were carried out with 10 students from the similar sample. Quantitative data analysis was conducted using SPSS, employing exploratory factor analysis, descriptive analysis, and multiple linear regression analysis. Thematic analysis was used to categorize, assess, and explain the feedback from focus group members.